Characterization of Free-nets in the United States and Canada: Facing History and Managing the Future - Chase, Timothy S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The explosion in the number of Free-Nets and their organizing committees over the past two years attests to the popularity of community-based computing. But, the goal of these organizations is farther reaching than merely strength of numbers; they want to change their communities for the better. In order to assure an important and relevant place in the community, Free-Nets must face the history of the other community-based information service provider: the public library. Once this is done, Free-Nets must focus on achieving results, not merely on achieving continued existence.